Activation of the alternative complement pathway: clinical application of a new technique to measure fragment Ba. Issue 10 (October 1987) - Senaldi, G; Peakman, M; Alhaq, A; Makinde, V A; Tee, D E; Vergani, D
Abstract : A new laser nephelometric technique for the measurement of the alternative complement pathway fragment Ba has been developed. Activation of the alternative complement pathway was assessed in 16 patients with Gram negative bacteraemia, six with Gram positive bacteraemia, 20 with rheumatoid arthritis, and 18 healthy subjects. Patients with Gram negative bacteraemia had significantly higher values of Ba (median 14.8%) than controls (9.3%) (p less than 0.01), while patients with Gram positive bacteraemia and rheumatoid arthritis had values similar to those of controls (10.1% and 9.5%). The technique proved sensitive and precise, and is suitable for the routine laboratory evaluation of complement activation through the alternative pathway.